Analisis Peramalan Inflasi Di Kota Balikpapan Menggunakan Metode ARIMA - Lembang, Gebryani Rante; Silfiani, Mega; Fitria, Irma (SPECTA Journal of Technology, 2023)
Uncontrolled inflation is one of the problems in a country's economy. This is because inflation is used as a reference for monetary policy. However, controlling the inflation rate is relatively difficult to do. Therefore, an accurate inflation rate forecast is needed so that it can predict future inflation. This research aims to predict future inflation using the ARIMA method. The data used in this research is inflation in Balikpapan City from January 2016 to December 2022. From the analysis results, the best ARIMA method for predicting inflation in Balikpapan City is ARIMA([1,2,12],0,[6]) which has an RMSE value of 0.22886. Further research that can be carried out to improve the accuracy of Balikpapan City inflation forecasting is the use of combined methods or adding independent variables that are able to explain Balikpapan City inflation in the future.